2003
DOI: 10.1002/cne.10982
|View full text |Cite
|
Sign up to set email alerts
|

Connection from the dorsal column nuclei to the superior colliculus in the rat: Topographical organization and somatotopic specific plasticity in response to neonatal enucleation

Abstract: Somatosensory stimuli from the body to deep and intermediate strata of the superior colliculus (SC) are relayed from the dorsal column nuclei (DCN), gracile (GrN) and cuneate (CuN). Electrophysiological studies have shown that the somatosensory representation in SC is arranged into a map-like pattern. However, there is a lack of studies confirming a morphological correlate of such an organization. On the other hand, after neonatal enucleation in rodents, somatosensory inputs ascend from their normal terminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Surrounding the cerebral aqueduct in the tegmentum, the periaqueductal gray (PAG) receives afferents from the spinothalamic tract that transmit pain and temperature information. Interestingly, the DCN have also been shown to send contralateral projections via the ML LAC to the PAG (Figure 7; Barbaresi & Mensà, 2016; Björkeland & Boivie, 1984; García Del Caño, Uria, Gerrikagoitia, & Martínez‐Millán, 2004; Hazlett et al, 1972; Schroeder & Jane, 1971; Villanueva et al, 1998; Wiberg et al, 1987), which terminate somatotopically such that the Gr project to the caudal lateral PAG and the Cu to rostral lateral PAG (Barbaresi & Mensà, 2016).…”
Section: Dcn Projection Targets and Connectionsmentioning
confidence: 99%
“…Surrounding the cerebral aqueduct in the tegmentum, the periaqueductal gray (PAG) receives afferents from the spinothalamic tract that transmit pain and temperature information. Interestingly, the DCN have also been shown to send contralateral projections via the ML LAC to the PAG (Figure 7; Barbaresi & Mensà, 2016; Björkeland & Boivie, 1984; García Del Caño, Uria, Gerrikagoitia, & Martínez‐Millán, 2004; Hazlett et al, 1972; Schroeder & Jane, 1971; Villanueva et al, 1998; Wiberg et al, 1987), which terminate somatotopically such that the Gr project to the caudal lateral PAG and the Cu to rostral lateral PAG (Barbaresi & Mensà, 2016).…”
Section: Dcn Projection Targets and Connectionsmentioning
confidence: 99%
“…Anatomical studies have clearly demonstrated that visual and somatosensory maps in the SC are constructed on the basis of a topographic arrangement of afferents to this structure (Nauta and van Straaten,1947; Lund et al,1980; Ndiaye et al,2002; García del Caño et al,2004). However, despite the fact that the acoustic environment is represented in a map‐like fashion, in contrast to the visual and somatosensory systems it does not appear to be based on a topographical arrangement of auditory afferent fibers (see Stein and Meredith,1993b, for review).…”
Section: Discussionmentioning
confidence: 99%
“…Surrounding the cerebral aqueduct in the tegmentum, the periaqueductal grey (PAG) receives afferents from the spinothalamic tract that transmit pain and temperature information. Interestingly, the DCN have also been shown to send contralateral projections via the ML LAC to the PAG (Figure 7) (Barbaresi & Mensà, 2016;Björkeland & Boivie, 1984;García Del Caño, Uria, Gerrikagoitia, & Martínez-Millán, 2004;Hazlett et al, 1972;Villanueva et al, 1998;Wiberg et al, 1987), which terminate somatotopically such that the Gr project to the caudal lateral PAG and the Cu to rostral lateral PAG (Barbaresi & Mensà, 2016).…”
Section: System 4: Brainstem System Periaqueductal Greymentioning
confidence: 99%